2020
DOI: 10.1088/1755-1315/476/1/012063
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low-density polyethylene (LDPE) addition to the characteristics of asphalt mixture

Abstract: Improving the quality of asphalt by adding additives like polymers, one of which is Polyethylene mixed in the AC-WC asphalt mixture. This research aims to determine the effect of adding Polyethylene on the characteristics of AC-WC asphalt mixture and bitumen properties. Polyethylene used is the Low-Density Polyethylene (LDPE) type, especially thin plastic bags with 0%, 4%, 5%, 6%, 8%, 10%, 15% and 20% contents of the asphalt weight. The Marshall Test is conducted to determine the value of stability and flow, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Asphalt-mix properties can be further improved by using more advanced techniques with other modifiers, preferably with waste materials. Lubis et al (2020) investigated that LDPE bags with different percentages of weight of asphalt were added and tests were conducted for the determination of stability and permanent deformation. The results showed that utilization of LDPE in the asphalt mix up to a specific content (6%) can improve the performance of the HMA mix, especially decreasing the rate of deformation.…”
Section: Introducti̇on and Literature Revi̇ewmentioning
confidence: 99%
“…Asphalt-mix properties can be further improved by using more advanced techniques with other modifiers, preferably with waste materials. Lubis et al (2020) investigated that LDPE bags with different percentages of weight of asphalt were added and tests were conducted for the determination of stability and permanent deformation. The results showed that utilization of LDPE in the asphalt mix up to a specific content (6%) can improve the performance of the HMA mix, especially decreasing the rate of deformation.…”
Section: Introducti̇on and Literature Revi̇ewmentioning
confidence: 99%